(untitled) (Eurasian Journal of Philology Science and Education, 2019)
This article outlines the national-cultural features of the concept «Motherland» in the Russian language. The image of the motherland, native land is one of the most significant concepts for any person: without a country, a person feels detached from the people, from the nation. The sacred image of the Motherland is formed in childhood, is praised in literature, oral folk art, is reflected in proverbs and sayings, popular expressions and wise sayings. There is also a broad explanation of the words «Motherland». The history of the origin of the word «Motherland». At the end of the article, the similarities and differences of the Russian language in the Kazakh language are shown.